Effects of the health insurance coverage extension on the use of outpatient services among small children in rural China - Kawazoe, Nobuo (Nagoya J Med Sci, 2015)
A new public health insurance scheme has been gradually introduced in rural provinces in China since 2003. This would likely cause an increment in the use of health services. It is known that the association between health insurance coverage and health service utilization varies among different age groups. This study aims to examine the association between extending health insurance coverage and increment in outpatient service utilization of small children in rural China, and to identify other factors associated with the outpatient service utilization. A household survey was conducted in 2 counties in north China in August 2010, targeting 107 selected households with a child aged 12–59 months. The questionnaire included modules on demographic information such as ages of children and parents, enrollment status of health insurance, the number of episodes of illness as perceived by parents, month of incidence of episode and outpatient service utilization at each episode. Based on the utilization at each episode of illness, a random effects logistic regression model was employed to analyze the association. It was found that eligibility for the reimbursement of outpatient medical expenses was not significantly associated with decision to seek care or choice of health facility. This might be in part due to the low level of reimbursement which could discourage the use of insured, and to the close relationship with village clinic workers which would encourage the use of uninsured. Three other factors were significantly associated with increment in the outpatient service utilization; age of children, mother’s education, and number of children in a household.